Effectiveness of Montessori Art Learning on Fine Motor Skills of Children with Moderate Intellectual Disabilities in a Special Primary School - Anis Tuing Isti Nur Syarifah; Ishartiwi Ishartiwi; Leni Ambar Cahyani; Farah Prihandini (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2026)
This study aimed to investigate the effectiveness of Montessori Practical Life activity–based visual art learning in improving fine motor skills of children with moderate intellectual disabilities in special school. The research employed a quasi-experimental design with one group pre-test and post-test. Four students with moderate intellectual disabilities participated as subjects. Data were collected using performance tests adapted from Bruni Fine Motor Components and analysed with the Wilcoxon Signed Ranks Test. The findings indicate that Montessori Practical Life activity–based visual art learning significantly enhanced fine motor skills, as evidenced by the rejection of the null hypothesis (T count = 0, T table = 0) after eight sessions. Improvements were observed in several indicators, including body stability, bilateral coordination, eye–hand coordination, and dexterity. The effectiveness of this approach can be attributed to the alignment between the objectives of visual art learning and Montessori Practical Life activities, the freedom provided for children to explore activities independently, and the contextualization of tasks with daily routines. The integration of Practical Life activities—such as moving objects with a spoon before colouring and drawing, using tongs before cutting, and folding cloth before paper folding—helped strengthen finger movements. Montessori Practical Life–based visual art learning proves effective in enhancing fine motor skills of children with moderate intellectual disabilities in Special Primary School.